Določanje velikosti in oblike krošnje s pomočjo krošnjemera - Čarman, Rok (Gozdarski vestnik, 2008)
We tested two methods for measuring the volume and surface of beech and sprucetree crowns. The first method is based on an instrument called crown window, by means of which the volumes and surfaces of crowns were measured in sections, whereas the measurement according to the other method is based on geometric shapes. The sample comprised 60 beech and 40 spruce trees. We found major discrepancies in the measurements, especially with the sunny part of thebeech tree crown. The measurements tally to a greater extent with the spruce tree. Indicators of the shape of the crown mainly change with the thickness of the tree. When establishing the dependence of the increment on the crown parameters, we realized that with the beech tree the sunny crown more strongly affects the increment than the shady part of the crown, whereas it is just the opposite with the spruce tree.
Keywords: krošnja; oblika; volumen; površina; Fagus sylvatica L.G; Picea abies (L.) Karst.; prirastek